2003
DOI: 10.1029/2002jd002358
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative sampling using an Aerodyne aerosol mass spectrometer 1. Techniques of data interpretation and error analysis

Abstract: [1] The aerosol mass spectrometer (AMS), manufactured by Aerodyne Research, Inc., has been shown to be capable of delivering quantitative information on the chemical composition and size of volatile and semivolatile fine airborne particulate matter with high time resolution. Analytical and software tools for interpreting the data from this instrument and generating meaningful, quantitative results have been developed and are presented here with a brief description of the instrument. These include the conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
532
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 480 publications
(547 citation statements)
references
References 36 publications
12
532
1
2
Order By: Relevance
“…straight and level runs) will be smaller, being inversely proportional to the square root of the averaging time. Information on Q-AMS ambient sampling , data quantification (Allan et al, 2003) and mass spectrum deconvolution can be found elsewhere. As well as mass loadings for various species, speciated mass size distributions and mass spectra (which can provide some information on the organic aerosol functionality; Zhang et al, 2005) are obtained.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…straight and level runs) will be smaller, being inversely proportional to the square root of the averaging time. Information on Q-AMS ambient sampling , data quantification (Allan et al, 2003) and mass spectrum deconvolution can be found elsewhere. As well as mass loadings for various species, speciated mass size distributions and mass spectra (which can provide some information on the organic aerosol functionality; Zhang et al, 2005) are obtained.…”
Section: Methodsmentioning
confidence: 99%
“…This was accomplished by correcting the data using Equation (3), taken from Allan et al (2003), which corrects data for a reduction in gas phase nitrogen (the largest signal seen in the Q-AMS) due to a reduction in both electron multiplier performance throughout the flight, and also due to a reduction in mass flow rate into the instrument. AB 0 and Q 0 , and AB t and Q t represent the signal at m/z 28 (N 2 + ) and the mass flow rate at the time of IE calibration (preor post-flight) and at time t during measurement, and I t is the recorded signal at any m/z at a time t.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ambient-pressure sample containing aerosol particles enters the instrument through a 130 mm critical orifice, after which particles are collimated using the aerodynamic focusing lens mentioned above [Liu et al, 1995a[Liu et al, , 1995b. Because of the transmission efficiency of this lens, the Q-AMS measures particles with vacuum aerodynamic diameters (D va ) between 40 nm and 1 mm; this measurement is typically referred to as submicron [Liu et al, 1995a[Liu et al, , 1995bJayne et al, 2000;Allan et al, 2003], although the range of 100% transmission of particles is 60 to 600 nm. No correction was applied to account for sub-100% transmission of particles with diameters smaller than 60 and greater than 600 nm.…”
Section: Measurementsmentioning
confidence: 99%
“…This instrument employs thermal desorption, 70 eV electron ionization, and a quadrupole mass spectrometer. Data were processed and quality assured using the procedures described by Jimenez et al [2003] and Allan et al [2003Allan et al [ , 2004a and employed in conjunction with the pressuredependent calibrations and corrections described by Crosier et al [2006] needed for aircraft operation. Mass concentrations are reported from the Q-AMS (see section 5) for the total nitrate, organic, sulphate and ammonium component masses in the aerosol.…”
Section: Compositionmentioning
confidence: 99%